Challenges in English-medium instruction classes among engineering major students at Bangladeshi private universities - Md. Tarikul Islam; Md. Kamrul Hasan; Mohd. Moniruzzaman Akhand (Studies in English Language and Education)
Tertiary students in Bangladesh predominantly come from Bengali Medium Instruction (BMI) backgrounds and transition to English Medium Instruction (EMI) when pursuing higher education at private universities. This shift represents a critical transition phase from Bengali to English instruction. This study aimed to explore the challenges faced by Engineering major students during this transition at private universities in Bangladesh. Adopting a mixed-methods approach with a convergent parallel design, the study placed equal emphasis on quantitative and qualitative data. Quantitative data were collected through a survey of 301 respondents, while qualitative data were gathered via focus group interviews with 10 respondents using a random sampling technique. Descriptive analysis of the survey data was conducted using SPSS, and the interview data were analysed thematically. The survey results revealed that students faced significant challenges in EMI classrooms, including difficulties in understanding lectures, preparing assignments, conveying knowledge in exam scripts, and delivering presentations. The interviews provided deeper insights into these challenges. This study serves as an eye-opener, emphasizing the need for solutions to address the difficulties encountered by first-year engineering students during this transitional phase. It also recommends further research to examine the effectiveness of structured bridging programs in mitigating the linguistic gaps and challenges identified in this study.